Implementation of Event Management Stages in the Hybrid Event “ITDRI ConFes 2023” - Friqkia Inka Syahputri; Rah Utami Nugrahani (PT ARRUS Intelektual Indonesia, 2024)
The digital disruption era has significantly impacted people’s lives, with the internet becoming an integral part of modern society. This has also affected the marketing communication sector, particularly in the implementation of events. Hybrid events, which allow audiences to join from flexible locations and times, have emerged as a new trend. PT Telekomunikasi Indonesia Tbk, a State-Owned Enterprise engaged in Information and Communication Technology services and Telecommunications networks, has organized hybrid events to accelerate digital transformation in Indonesia. However, there are obstacles to overcome for smooth implementation. The design of the work “Implementation of Event Management Stages in the Hybrid Event “ITDRI ConFes 2023” PT Telekomunikasi Indonesia Tbk” aims to explain the stages of implementing a hybrid event according to Goldblatt's event management stages. The author uses participant observation, documentation, theoretical review, and interviews to design this work. The result is the ITDRI Conference & Festival 2023, which applies the event management process with Joe Goldblatt's theory, including the stages of Research, Design, Planning, Coordination, and Evaluation. Keywords: Event Hybrid, ITDRI ConFes 2023, Marketing Communication, Technology Development, Digital Transformation